A rare manifestation of atrial fibrillation in the presence of Wolff-Parkinson-White syndrome: tachycardia-induced cardiomyopathy - Aleks Değirmencioğu; Gültekin Karakuş; Erkan Baysal; Ertuğrul Zencirci; Nazmiye Çakmak (Türk Kardiyoloji Derneği Arşivi, 2014)
We report a 68-year-old man who presented with heart failure and atrial fibrillation (AF) with rapid ventricular response and wide QRS complexes. Tachycardiainduced cardiomyopathy (TIC) due to persistent AF developing on the basis of Wolff-Parkinson-White (WPW) syndrome was considered. Signs and symptoms of heart failure improved with restoration of sinus rhythm. This case suggested that persistent AF in a patient with WPW syndrome is one of the rare causes of TIC.